Efficiency and competitiveness of Rhizobium leguminosarum bv. phaseoli strains in field beans - Pereira, João Carlos; Vidor, Caio; Lovato, Paulo Emílio; Penteado, Alberto de Figueiredo (Pesquisa Agropecuaria Brasileira, 1991)
Two experiments were conducted in greenhouse with sand-nutrient solution or soil (Passo Fundo-Oxisol) to evaluate effectiveness and competitiveness for nodules sites among R. leguminosarum bv. phaseoli strains, resistant or sensitive to antibiotics when used as single or multi-strain inoculant on Phaseolus vulgaris (Cultivar Turrialba-4). Nodule typing showed double nodule occupancy by strains in both experiments. Resistance to antibiotics did not alter antigenic characteristics of the strains but some mutants were less competitive as compared to the parent strain. Some mutants resistant to streptomycin reverted to the sensitive type culture, varying from 13 to 32%. In the multi-strain inoculant (SEMIA 487 + SEMIA 487-2 + SEMIA 487-Nov) strain SEMIA 487-2 (resistant to streptomycin) occupied 82% of the nodules, whereas strain SEMIA 487-Nov (resistant to novobiocin) occupied 54%. Nodule typing also demonstrated a high competition of strain SEMIA 4002-S1 (resistant to streptomycin) for nodule sites.